Reconnecting when network ties go dormant : reviving a professional relationship isn't as simple as it looks : new research uncovers three key elements for successfully refreshing an inactive tie, and avoiding disastrous missteps - Rondi, Emanuela; Levin, Daniel Z.; De Massis, Alfredo (MIT Sloan Management Review, 2023)
Reviving an inactive social connection might seem as simple as reaching out to someone and starting a conversation, but reestablishing a professional relationship takes more care. New research has found that there are three key elements to refreshing a dormant tie successfully: remembering each other well, catching up on relevant experiences, and perceiving the relationship similarly. The researchers discuss how best to reestablish positive professional connections and avoid awkward missteps.